ICT approach to defuse the cybercriminal sedition dimension of Telangana movement - Madan Mohan, K; P. Premchand, Dr; K. Chandra Sekharaiah, Dr; Santhoshi, N (International Journal of Engineering and Technology, 2018)
Cybercrime refers to Internet usage involving any illegal activity. Cybercrimes are becoming galore throughout the length and breadth of the world owing to the increased Internet usage and the human capital involved in the usage. In India also, the same phenomenon is found as the nation has vast population. Undesirably, cybercrimes are percolating into some university academic environments. In our earlier work, we presented many facets of multiple cybercrimes in the JNTUH academic environment. The cybercrimes perpetrated, in the context of the Telangana Movement, w.r.t. the violations of State Emblem of India (Prevention of Improper Usage) Act 2005, u/s 66C-ITA2000-2008 were registered with FIRs. The cybercrime of sedition is not registered yet. Our research work explored in this regard. Under the cybercriminal Government of Telangana (CGoT) has been purportedly prevalent the JNTUHJAC, during 2011â€“2014 approx., as indicated in the website, http://jntuhjac.com, traceable through the cyber forensic web crawler tool wayback machine. Note worthily, the crime got registered against identity theft under Sec. 66-C under IT Act 2000-2008 whereas the complaint was against Sedition crime. The culprit website of JNTUHJAC organization under CGoT was operational in the JNTUH University before the enactment of Andhra Pradesh Reorganization Act 2014 and through that approx. 2000 registrations were obtained for the organizations. We present, in the case study, the many facets of the moot cybercrime issues related to the JNTUH University academic environment and how they are handled by means of the RTI Act 2005 for an empirical approach for impact on the law enforcement agencies to get alert and register the crime under sedition law violation in order to ensure that recurrence of such situations is prevented.Â Â